Perceptions and Attitudes of Indonesian Teachers towards the Simplication of Learning Implementation Plan based on Permendikbud No. 14 Years 2019 - Sunan Fatwa Rosfi; Syamsudduha Syamsudduha; Sultan Sultan (INSIGHT: Indonesian Journal Social Studies and Humanities, 2022)
Abstract. This study aims to: (1) obtain empirical data regarding the perceptions and attitudes of Indonesian language teachers at the Mallusetasi District Junior High School, Barru Regency towards the simplification of the Learning Implementation Plan (RPP) based on Permendikbud No. 14 of 2019; (2) determine the factors that influence the perceptions and attitudes of Indonesian language teachers at the Mallusetasi District Junior High School, Barru Regency towards the simplification of the Learning Implementation Plan (RPP). This type of research is qualitative research. This research was conducted in all junior high schools in Mallusetasi District, Barru Regency. Data collection was carried out during August - September 2021. The research design used was descriptive qualitative. The focus of this research is the perception and attitude of Indonesian teachers towards the simplification of lesson plans and the factors that influence the perceptions and attitudes of Indonesian teachers towards the simplification of lesson plans. The source of research data, namely Indonesian language teachers who teach at SMP Mallusetasi District, Barru Regency. Data collection techniques were carried out by conducting interviews about the perceptions and attitudes of Indonesian language teachers towards the simplification of lesson plans. The research instrument used is the interview guide. Keywords: Simplification of lesson plans, perceptions, attitudes